2020
DOI: 10.1186/s42408-019-0064-6
|View full text |Cite
|
Sign up to set email alerts
|

The influence of repeated prescribed fire on decomposition and nutrient release in uneven-aged loblolly–shortleaf pine stands

Abstract: Background: Repeated use of prescribed fire in Southern US pine stands has the potential to alter litter quality as well as forest floor mineralization, which may reduce nutrient availability. There are few studies that have investigated the effects of prescribed fire on litter decomposition in stands with frequent, partial harvests. To better understand the effects of the long-term use of prescribed fire coupled with periodic harvesting, we monitored foliar litter mass loss and nutrient dynamics in three lobl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 49 publications
2
5
1
Order By: Relevance
“…The significant changes in the extractable phosphorus concentration in our study were inconsistent with other findings [5,7], who reported no difference in phosphorus after a burn. Even though we detected a significant decline in the available phosphorus, the concentrations of phosphorus in the soil were relatively low across the different times and not at a more available level of concentration in the soil [18].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The significant changes in the extractable phosphorus concentration in our study were inconsistent with other findings [5,7], who reported no difference in phosphorus after a burn. Even though we detected a significant decline in the available phosphorus, the concentrations of phosphorus in the soil were relatively low across the different times and not at a more available level of concentration in the soil [18].…”
Section: Discussioncontrasting
confidence: 99%
“…Even though we detected a significant decline in the available phosphorus, the concentrations of phosphorus in the soil were relatively low across the different times and not at a more available level of concentration in the soil [18]. Significant changes in potassium agreed with [5], who found a significant increase in potassium after a fire, but contradicts [7], who found no significant change in potassium after a burn. Even though there were significant differences between time frames and burn intervals, they were not enough to effectively change the level of potassium [18].…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Postfire litter decomposition in low-latitude coniferous forests is characterized by contradictory results. A litterbag study of pine litter decomposing in Arkansas, USA, revealed a minimal difference in mass loss and nutrient dynamics between burned and control forests [31]. Other research even found enhanced decomposition in a postfire period in the one-seed juniper woodland of New Mexico, USA [32].…”
Section: Introductionmentioning
confidence: 99%
“…Its loss mainly occurs through leaching from the decomposing residues [9,39], being easily removed even in early stages of the process [40]. Releases of this nutrient have been evidenced in litter of different species of Eucalyptus and Pinus [3,[41][42][43].…”
Section: Discussionmentioning
confidence: 99%